Hepatitis B virus-induced CD4 lymphocytopenia: A rare cause of progressive multifocal leukoencephalopathy - Mishra, Amar Kumar; Kumar, Sanjay; Agasti, Niraja; Guha, Gautam; Ghosh, Saikat; Mohanty, Bijendra; Ngullie, Pideno S; Mukherjee, Joydeep (Asian Journal of Medical Sciences, 2022)
Progressive multifocal leukoencephalopathy (PML) is a rare subacute-onset fatal demyelinating disease of the central nervous system caused by the John Cunningham (JC) virus. It usually occurs in impaired cell-mediated immunity settings such as lymphoproliferative disorders, chronic infective or granulomatous conditions on immunosuppressive medications, and human immunodeficiency virus infection. It also appears very rarely with idiopathic CD4 lymphocytopenia. We present a case of PML with visual field defect, progressive motor impairment, behavioral alteration, and dementia. Magnetic resonance imaging had features of asymmetric non-enhancing hyperintense subcortical white matter lesions in the background of chronic active hepatitis B infection. To the best of our knowledge, this is the first case report of CD4 lymphocytopenia associated PML following chronic hepatitis B infection.